Imatinib-induced haematuria necessitating drug discontinuation. Issue 3 (October 2020) - Hemakumar, Anandu; Pavithran, Keechilat
Gastrointestinal stromal tumours are rare neoplasms of the gastrointestinal tract that are mesenchymal in origin. The introduction of tyrosine kinase inhibitors resulted in significant improvement in survival of patients with gastrointestinal stromal tumour even in advanced disease conditions. A 43-year-old adult male who is a known case of gastrointestinal stromal tumour of the stomach, on adjuvant therapy with imatinib, presented with a history of gross haematuria of several episodes as well as persistent microhaematuria and was evaluated for the same. He was investigated for all possible causes, but all were negative. The patient was advised to withhold imatinib. Haematuria resolved 1 month after stopping imatinib. Then it was rechallenged. He had recurrence of symptoms, so it was discontinued. In view of the temporal relation of haematuria and administration of imatinib, a diagnosis of imatinib-induced haematuria was made.